MP Transparency, Communication Links and Social Media: A Comparative Assessment of 184 Parliamentary Websites - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2013)
Parliamentary websites (PWs) can potentially enhance the quality of government by providing information and communication links that stimulate political awareness, deliberation and participation. This article focuses on two particular uses of PWs that can facilitate communication between constituents and their Members of Parliament: provision of MP contact and background information; and links to social media. Through a seminal empirical examination of all 184 functioning lower house and unicameral PWs around the world, this study found that although PWs in wealthy democracies generally provide more MP information, the majority of PWs are deficient in providing basic MP information to citizens and utilizing linkages to social media. By contrast, some non-democratic states and newly democratized countries, especially those with compulsory voting, display a relatively high level of MP transparency and social media connectivity.